2017
DOI: 10.1016/j.livres.2017.08.005
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormal expression of TFIIIB subunits and RNA Pol III genes is associated with hepatocellular carcinoma

Abstract: The levels of the products of RNA polymerase III-dependent genes (Pol III genes), including tRNAs and 5S rRNA, are elevated in transformed and tumor cells, which potentiate tumorigenesis. TFIIB-related factor 1 (Brf1) is a key transcription factor and specifically regulates the transcription of Pol III genes. In vivo and in vitro studies have demonstrated that a decrease in Brf1 reduces Pol III gene transcription and is sufficient for inhibiting cell transformation and tumor formation. Emerging evidence indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 116 publications
(210 reference statements)
0
15
0
Order By: Relevance
“…[12][13][14][15]. Chronic alcohol consumption causes liver fibrosis and cirrhosis and enhances the risk of HCC [33]. Alcohol was classified as carcinogenic by the International Agency for Research on Cancer (IARC) [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15]. Chronic alcohol consumption causes liver fibrosis and cirrhosis and enhances the risk of HCC [33]. Alcohol was classified as carcinogenic by the International Agency for Research on Cancer (IARC) [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Decrease of Brf1 results in reduction of Pol III gene levels; the reduction is able to repress transformation of cells and xerography formation of the nude mouse [ 12 15 ]. Chronic alcohol consumption causes liver fibrosis and cirrhosis and enhances the risk of HCC [ 33 ]. Alcohol was classified as carcinogenic by the International Agency for Research on Cancer (IARC) [ 34 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol feeding of mice promotes mammary tumorigenesis [36, 37]. Cell culture studies have demonstrated that the transcription products of RNA Pol III genes were elevated in both transformed and tumor cells [19, 20, 29, 33, 6669], while the inductions of Pol III genes by alcohol in tumor cells were much higher than those in nontumor cells [33]. Consistent with this idea, enhanced Pol III gene transcription is required for oncogenic transformation of cells [19, 20, 29].…”
Section: Deregulation Of Rna Pol III Genes and Breast Cancermentioning
confidence: 99%
“…During cell cycle, the transcription of RNA pol III is regulated to ensure normal cellular growth ( 10 , 11 ). Previous studies reported that RNA pol III activity plays a key role in the deregulation of a variety of cancers, regardless of tissue types ( 12 , 13 ). Deregulation of TFIIIB-mediated transcription is an important factor in tumor development ( 14 ).…”
Section: Introductionmentioning
confidence: 99%